Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

If f(x)=5x0+4x-3 then f(a)=

Sagot :

Answer:

f=

1

/4

y+

−1

/2

Step-by-step explanation:

Let's solve for f.

y=5x^0+4x−3

Step 1: Flip the equation.

4x+2=y

Step 2: Add -2 to both sides.

4x+2+−2=y+−2

4x=y−2

Step 3: Divide both sides by 4.

4x

/4

=

y−2

/4

x=

1

/4

y+

−1

/2

=f=

1

/4

y+

−1

/2

brainliest please?